Causas do desmatamento e suas consequências agroambientais e socioeconômicas no Haiti - Joseph, Adelaine Delorieux (Universidade Federal de São Carlos, 2025)
Deforestation is one of the major global threats to biodiversity and climate stability. Its most recurrent causes are associated with anthropogenic activities such as agricultural expansion, timber and charcoal extraction, mining, forest fires, burning practices, and infrastructure development, resulting in the progressive reduction of natural forests. In Haiti, this phenomenon takes on historical and structural dimensions, linked to the colonial legacy, institutional fragility, and persistent socioeconomic inequalities. This study aimed to provide a deep and multiscalar understanding of the causes of deforestation in Haiti and its agro-environmental and socioeconomic consequences, focusing on two communes in the northeast of the country (Mombin-Crochu and Vallières), whose populations are predominantly poor and dependent on wood as their primary energy source. The qualitative methodology involved two complementary stages: (i) a systematic review of the scientific literature based on the analysis of 27 publications, and (ii) participatory fieldwork, including focus groups with residents and semi-structured interviews with local authorities. The results show that deforestation in Haiti reflects a process of environmental coloniality, reproduced through poverty, dependence on wood for energy, and the absence of sustainable socioeconomic alternatives. The main consequences identified include soil erosion, landslides, reduced agricultural fertility, and the intensification of extreme climate events. We observed significant convergence between scientific data and local knowledge, demonstrating that residents possess ecological awareness and diagnoses consistent with technical literature. The proposals presented by participants such as participatory reforestation, sustainable use of forest resources, and a just energy transition point to concrete pathways for public policies grounded in ecological justice and the appreciation of community-based knowledge, reaffirming that environmental reconstruction in Haiti requires both historical repair and a decolonial ecological transition.

Debwazman reprezante youn nan pi gwo menas mondyal kont biyodivèsite ak estabilite klimatik. Pi fò nan kòz li yo gen rapò ak aktivite imèn, tankou agrikilti ki ap elaji, eksplwatasyon bwa ak chabon, min, dife nan forè, boule tè ak konstriksyon enfrastrikti, sa ki lakòz yon pwogrè nan rediksyon forè natirèl yo. Nan peyi Ayiti, fenomèn sa a gen rasin istorik ak estriktirèl, ki lye ak eritaj kolonyal la, feblès enstitisyon yo ak inegalite sosyo-ekonomik ki pèsistan. Etid sa a chache bay yon konpreyansyon pwofon ak milti-nivo sou kòz deforestasyon an Ayiti ak konsekans agro-anviwònmantal ak sosyo-ekonomik li yo, atravè analiz de de komin nan nòdès peyi a (Mombin-Crochu ak Vallières), kote popilasyon an majoritèman pòv e depann de bwa kòm prensipal sous enèji. Metodoloji a, ki baze sou yon apwòch kalitatif, te gen ladan li de etap konplemantè: (i) yon revizyon sistematik literati syantifik, ki te enkli analiz 27 piblikasyon, epi (ii) yon travay teren patisipatif, ki te fèt atravè gwoup fokal ak peyizan yo, ak entèvyou semi-estriktire ak otorite lokal yo. Rezilta yo montre ke debwazman an Ayiti reflete yon pwosesis kolonyalite anviwònmantal, ki repwodui lamizè, depandans sou bwa kòm sous enèji ak absans altènativ sosyo-ekonomik dirab. Nou idantifye kòm prensipal konsekans ewozyon tè, glisman teren, rediksyon randman agrikòl ak agravasayon evènman klimatik ekstrèm yo. Nou te obsève yon gwo konvèjans ant done syantifik yo ak konesans lokal yo, ki montre ke abitan yo gen yon konsyans ekolojik e dyagnostik anviwònmantal peyizan yo ann amoni ak literati teknik la. Pwopozisyon patisipan yo tankou reforestasyon patisipatif, itilizasyon dirab resous forestye yo ak yon tranzisyon enèjetik jis, ofri chemen konkrè pou politik piblik ki chita sou jistis ekolojik ak valorizasyon konesans kominotè yo, konfime ke rekonstriksyon anviwònmantal Ayiti mande an menm tan reparasyon istorik ak yon tranzisyon ekolojik vrèman dekolonyal.
Causes of deforestation and its agro-environmental and socioeconomic consequences in Haiti
Kòz debwazman ak konsekans agro-anviwònmantal ak sosyo-ekonomik li yo ann Ayiti
Keywords: Desmatamento; Deforestation; Deforestasyon; Haiti; Impactos Agroambientais; Impactos socioeconômicos; Mombin-Crochu; Vallières; Agro-environmental impacts; Socio-economic impacts; Ayiti; Enpak sosyoekonomik; Enpak agroanviwonmantal; CIENCIAS AGRARIAS; 1. Erradicação da Pobreza; 13. Ação contra a Mudança Global do Clima; 10. Redução das Desigualdades